A clinical trial comparing Lanconone® with ibuprofen for rapid relief in acute joint pain. Issue 1 (December 2016) - Girandola, Robert; Srivastava, Shalini; Loullis, Costas
Abstract Background To study the effect of Lanconone® (1000 mg) on acute pain on exertion as compared to the standard of care, Ibuprofen (400 mg). Method The study recruited 72 subjects diagnosed with mild to moderate knee joint pain on exertion. Subjects with Pain Visual Analogue Scale of more than 40 mm were included. Uphill walking was provided as the stressor using Naughton's protocol on a treadmill. The subjects walked for 10 minutes continuously followed by a rest period and baseline pain score for index knee joint was recorded. Subjects were administered a single dose of Lanconone® (1000 mg)/Ibuprofen (400 mg). Thereafter the same stressor was provided at 0.5, 1, 2, 3, 4, and 6 hours, subsequently, pain scores were recorded on a visual analogue scale. Double stopwatch method was used to evaluate the onset of pain relief and time taken to meaningful pain relief. Result Both Lanconone® and Ibuprofen showed the first perceived pain relief at65.31 ± 35.57 mins as compared to60.82 ± 32.56 mins respectively. The mean time taken to experience meaningful pain relief in Lanconone® group was196.59 ± 70.85 mins compared to167.13 ± 71.41 mins amongst Ibuprofen group. The meaningful pain relief continued for 6 hours. Conclusion The current study successfully demonstrated rapid pain-relieving potential of Lanconone® which was comparable to Ibuprofen. No adverse event related to the interventions was reported in the study. Trial registration Clinical trials.govNCT02417506 . 21 January 2015.